The relations of mothers’ negative expressivity to children’s experience and expression of negative emotion - Valiente, Carlos (2004)
Guided by the heuristic model proposed by Eisenberg et al. [Psychol. Inq. 9 (1998) 241], we examined the relations of mothers’ reported and observed negative expressivity to children’s (N = 159; 74 girls; M age = 7.67 years) experience and expression of emotion. Children’s experience and/or expression of emotion in response to a distressing film were measured with facial, heart rate, and self-report measures. Children’s heart rate and facial distress were modestly positively related. Children’s facial distress was significantly positively related to mothers’ reports of negative (dominant and submissive) expressivity; the positive relation between children’s facial distress and mothers’ observed negative expressivity approached the conventional level of significance. Moreover, mothers’ observed negative expressivity was significantly negatively related to children’s heart rate reactivity during the conflict film. The positive relation between children’s reported distress and mothers’ observed negative expressivity approached the conventional level of significance. Several possible explanations for the pattern of findings are discussed.